Development of a Practical Synthetic Method for Clinical Candidate 3-(2-{3-[(2,4-Diamino-6-ethylpyrimidin-5-yl)oxy]propoxy} phenyl)propanoic acid (P218) and Its Hydroxylated Metabolites - Vorasin, Onanong; Phumjan, Tanawat; Saepua, Siriporn; Iwaniuk, Daniel; Kamchonwongpaisan, Sumalee; Yuthavong, Yongyuth; Thongpanchang, Chawanee; Srimongkolpithak, Nitipol (Synthesis, 2023)
3-(2-{3-[(2,4-Diamino-6-ethylpyrimidin-5-yl)oxy]propoxy}phenyl)propanoic acid, known as P218, has demonstrated great potency and safety in preclinical and human studies. However, the previous synthetic methods for P218 gave low yields and required hazardous reagents and challenging procedures. In this study, we have successfully developed a decagram-scale synthetic route for P218 with practical and scalable methods for large-scale production. Furthermore, this is also a first report of a novel synthetic approach for P218-OH, a hydroxylated metabolite of P218, by modification of our discovery route. Our synthetic procedures for P218 and P218-OH are a significant advancement in drug development processes, including manufacturing processes and drug metabolism studies.
Keywords: P218; pyrimidine; antimalarial drugs; process development